Applying cover crop residues as diverse mixtures increases initial microbial assimilation of crop residue‐derived carbon. (25th March 2022) - Shu, Xin; Zou, Yiran; Shaw, Liz J.; Todman, Lindsay; Tibbett, Mark; Sizmur, Tom
Abstract: Increasing the diversity of crops grown in arable soils delivers multiple ecological functions. Whether mixtures of residues from different crops grown in polyculture contribute to microbial assimilation of carbon (C) to a greater extent than would be expected from applying individual residues is currently unknown. In this study, we used 13 C isotope labelled cover crop residues (buckwheat, clover, radish, and sunflower) to track microbial assimilation of plant residue‐derived C using phospholipid fatty acid (PLFA) analysis. We also quantified microbial assimilation of C derived from the soil organic matter (SOM) because fresh residue inputs also prime the decomposition of SOM. To consider the initial stages of residue decomposition, and preclude microbial turnover, we compared a quaternary mixture of residues with the average effect of their four components 1 day after incorporation. Our results show that the microbial biomass carbon (MBC) in the treatment receiving the mixed residue was significantly greater, by 132% (3.61 μg C g −1 ), than the mean plant residue‐derived MBC in treatments receiving the four individual components of the mixture. However, there was no evidence that the mixture resulted in any additional assimilation of C derived from native SOM than the average observed in individual residue treatments. We surmise that, during the initial stages of crop residue decomposition, a greater biodiversity of residues increases microbial assimilation to a greater extent than would be expected from applying individual residues either due to faster decomposition or greater carbon use efficiency (CUE). This might be facilitated by functional complementarity in the soil microbiota, permitted by a greater diversity of substrates, reducing competition for any single substrate. Therefore, growing and incorporating crop polycultures (e.g., cover crop mixtures) could be an effective method to increase microbial C assimilation in the early stages of cover crop decomposition. Highlights: The effect of mixing crop residues on assimilation of C by soil microbial biomass was investigated. The study is important due to recent interest in diverse cover crop mixtures for arable systems. Mixing crop residues enhanced the assimilation of plant residue‐derived C into microbial biomass. Growing and incorporating cover crop polycultures may enhance C storage in arable soils.